Particle Replication in Nonwetting Templates Nanoparticles with Tumor Selective Alkyl Silyl Ether Docetaxel Prodrug Reduces Toxicity - Chu, Kevin S. (2014)
[Image: see text] Delivery systems designed to have triggered release after passively targeting the tumor may improve small molecule chemotherapeutic delivery. Particle replication in nonwetting templates was used to prepare nanoparticles to passively target solid tumors in an A549 subcutaneous xenograft model. An acid labile prodrug was delivered to minimize systemic free docetaxel concentrations and improve tolerability without compromising efficacy.